Fundamentals of biochemistry : life at the molecular level - Voet, Donald Voet, Judith G. (Wiley, 2006)
: This text uses a more brief and qualitative approach to present biochemistry with chemical rigor, focusing on the structures of biomolecules, chemical mechanisms, and evolutionary relationships. It is written to impart a sense of intellectual history of biochemistry, an understanding of the tools and approaches used to solve biochemical puzzles, and a hint of the excitement that accompanies new discoveries. This edition has been thoroughly updated to reflect the most recent advances in biochemistry, particularly in the areas of genomics and structural biology. A new chapter focuses on cytoskeletal and motor proteins, currently one of the most active areas of research in biochemistry.